ANALYZING COALITIONS IN CHINA'S POLICY FORMULATION: REFORMING THE ROLE OF STATE-OWNED ENTERPRISES IN CHINA'S ENERGY SECTOR. (10th May 2016) - Efird, Brian; Lester, Leo; Wise, Ben
Abstract: We focus on the elite decision-making process in China, analyzing the formation of coalitions around particular policy options. We apply a framework that simulates collective decision-making processes (CDMP): the KAPSARC Toolkit for Behavioral Analysis (KTAB). KTAB facilitates the application of a Spatial Model of Politics, an open source model similar to Bueno de Mesquita's (1997) Expected Utility Model and the Senturion model (Abdollahian, et al 2006). KTAB provides a framework to understand logical consequences of subjective data inputs, enabling contrasting scenarios to be analyzed. We examine the interactions of actors' interests that drive China to reform its energy sector policies, in particular the structure of the Chinese National Petroleum Corporation (CNPC). In the case of private companies' entry into energy markets in China, we find that little reform is likely. The inertia of key actors holds back the potential for a significant opening of the energy sector. Despite the erosion of CNPC's political clout, there is little consensus for major reform to China's market position.